DINAMIKA ARAH KEPASTIAN HUKUM DI TENGAH TRANSFORMASI SOSIAL-BUDAYA DALAM PERSPEKTIF PEMIKIRAN MAZHAB SOCIOLOGICAL JURISPRUDENCE - Suliantoro, B. Wibowo (Jurnal Filsafat "WISDOM", 2007)
The simultaneous process of social-culture transformation emerges a complex problematic in the sector of law; especially it is related with the law certainty. The clash of values occurred intensively and extensively fixes a polemic whether the law must be stable or is always in changing. The law that is always in changing will leave a certainty as an essential character of law. On the contrary, the law that stable in its nature will turn up a problem, it will not accommodate the internal dynamic. The sect of Sociological Jurisprudence, in its effort tries to formulate a harmonious synthesis by positing the significant meaning of customary law and the written constitution as a tool of social live arrangement in order to manage it better. The certainty of law will be achieved throughout continuous dialog process between rationality and experience, between fact that happen in the social life and the ideal normative of juridical values those are formulated in constitution. The certainty of law can be approached properly if it is supported by professional lawyer apparatus that has high moral integrity. The task of judge is not only to be speaker of constitution but also to enforce the justice. Therefore, the law enforcer should has sensitive feeling in understanding the phenomena of social justice that is desired by society, formulating the social justice in the constitution, and implementing the constitution wisely.